2009
DOI: 10.1007/s00134-009-1715-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of paediatric alert criteria for identifying hospitalised children at risk of critical deterioration

Abstract: Evidence supporting the validity, reliability and utility of paediatric alert criteria is weak. Studies are needed to determine which physiological parameters or combinations of parameters, best predict serious adverse events. Prospective evaluation of validity, reliability and utility is then needed before widespread adoption into clinical practice can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 43 publications
2
90
0
6
Order By: Relevance
“…4 The PEWS can be differentiated into scoring systems and triggering systems. 1 A scoring system contains different parameters (eg, heart rates or respiratory rates). If these parameters show an increased deviation from normal values, the given scores are greater.…”
Section: Pediatric Early Warning Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The PEWS can be differentiated into scoring systems and triggering systems. 1 A scoring system contains different parameters (eg, heart rates or respiratory rates). If these parameters show an increased deviation from normal values, the given scores are greater.…”
Section: Pediatric Early Warning Scoresmentioning
confidence: 99%
“…1 A recent publication showed that early warning scores are needed to quickly identify critically ill patients in the emergency departments (EDs) so that treatment can be started without delay. 2 Moreover, the use of the same system in the ED and inpatient wards allows continuity for patient assessment.…”
mentioning
confidence: 99%
“…In paediatrics, there is currently no consensus on which specific observations should be used to predict deterioration in sick children (Chapman et al, 2010). A large number of PEWs (many un-validated) are in use within the United Kingdom (Roland et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, Pediatric Early Warning Score (PEWS) instruments have been developed and validated (5)(6)(7)(8)(9) for the last 10 years, for early identification of warning signs in hospitalized children's bedside. Their objective is to signal the team regarding the need for providing urgent care to patients at risk for serious events, by means of regular monitoring of clinical signs and pre-established criteria (10) . Published in 2005, the Brighton Paediatric Early Warning Score (BPEWS) or Monaghan PEWS is among the PEWS instruments.…”
Section: Introductionmentioning
confidence: 99%